2013
DOI: 10.1091/mbc.e13-08-0441
|View full text |Cite
|
Sign up to set email alerts
|

ER-associated SNAREs and Sey1p mediate nuclear fusion at two distinct steps during yeast mating

Abstract: Both SNAREs and Sey1p are required for efficient nuclear fusion during yeast mating. SNAREs appear to act at the step of nuclear envelope fusion, whereas Sey1p remodels the ER network to permit nuclear congression. In addition, SNARE sey1Δ double mutants reveal an Sey1p-independent, SNARE-mediated ER fusion pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…The endoplasmic reticulum (ER) is a network of endomembranes that envelops the nucleus as the nuclear envelope (Johnson and Porter, ), and extends to almost all organelles via vesicle transport and specialized contact sites (Bellucci et al ., ; Wang and Dehesh, ). ER‐localized translocons and the soluble N‐ethylmaleimide‐sensitive factor attachment protein receptors (SNAREs) are reported to mediate nuclear fusion during zygote formation in Saccharomyces cerevisiae (Brizzio et al ., ; Rogers et al ., ). To examine ER dynamics in sexual zygotes, we used ER‐Tracker Green to stain the membrane systems surrounding the nucleus and throughout the cell: a nearly identical pattern is seen in cells carrying Venus‐tagged SEC61A, a major component of ER‐translocons (Figure S5f,g; Mackinder et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…The endoplasmic reticulum (ER) is a network of endomembranes that envelops the nucleus as the nuclear envelope (Johnson and Porter, ), and extends to almost all organelles via vesicle transport and specialized contact sites (Bellucci et al ., ; Wang and Dehesh, ). ER‐localized translocons and the soluble N‐ethylmaleimide‐sensitive factor attachment protein receptors (SNAREs) are reported to mediate nuclear fusion during zygote formation in Saccharomyces cerevisiae (Brizzio et al ., ; Rogers et al ., ). To examine ER dynamics in sexual zygotes, we used ER‐Tracker Green to stain the membrane systems surrounding the nucleus and throughout the cell: a nearly identical pattern is seen in cells carrying Venus‐tagged SEC61A, a major component of ER‐translocons (Figure S5f,g; Mackinder et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Cells containing both a sey1 deletion and a mutant retrograde SNARE allele ( sec20-1 , ufe1-1 , use1-10AA , or use1-0layer ) have strong synthetic growth and ER structural defects not seen in either single mutant ( Anwar et al , 2012 ; Rogers et al , 2013 ). We hypothesized that homotypic ER fusion is mediated by two parallel pathways, one Sey1p mediated and the other SNARE mediated, and that only disruption of both pathways results in severe ER–ER fusion and growth defects.…”
Section: Resultsmentioning
confidence: 99%
“… Patel et al (1998) demonstrated that ER membranes isolated from ufe1-1 cells were defective in an in vitro ER–ER fusion assay. More recently, strong synthetic growth and ER structure defects were demonstrated for double mutants of sey1 Δ and the three ER-bound retrograde (Golgi-to-ER) SNAREs ( s oluble N -ethylmaleimide–sensitive factor a ttachment protein re ceptors) sec20 , ufe1 , and use1 ( Anwar et al , 2012 ; Rogers et al , 2013 ). Moreover, sey1 Δ ufe1-1 double mutants had an even slower rate of homotypic ER fusion than sey1 Δ or ufe1-1 single mutants ( Anwar et al , 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NE fusion itself depends on a surprisingly large number of snare proteins (Bos1, Sec20, Ufe1, Use1) – judging from investigation of crosses conducted at semi-permissive temperature - and the snare disassembly factor, Sec18 – judging from “2-step crosses” in which cells are first allowed to fuse while congression is reversibly inhibited [150, 165]. Earlier studies have also provided evidence for participation of the ATPase, Cdc48 [166].…”
Section: Karyogamymentioning
confidence: 99%